Evaluation of the healing potential of short-term ozone therapy for the treatment of diabetic foot ulcers - Sun, Haojie; Heng, Hao; Liu, Xuekui; Geng, Houfa; Liang, Jun (Frontiers in Endocrinology, 2024)
Background:The availability of research on short-term ozone therapy for diabetic foot ulcers (DFUs) is limited, and even when it is accessible, it mainly comprises of basic analysis conducted during long-term ozone therapy. This study was to evaluate the efficacy of short-term ozone therapy in promoting wound healing in DFUs.: A retrospective analysis was conducted on 89 patients with type 2 diabetes complicated by DFUs. The patients were divided into two groups: ozone therapy group (n=41) and control group (n=48). Wound condition, change of bacterial types, changes in inflammatory indicators (erythrocyte sedimentation rate [ESR], C-reactive protein [CRP], and procalcitonin [PCT]), vascular endothelial growth factor (VEGF), cytokines [Interleukin 6 (IL-6) and tumor necrosis factor-α(TNF-α)], and oxidative stress levels (superoxide dismutase [SOD], malondialdehyde [MDA], and total antioxidant capacity [T-AOC]) were observed pre-treatment and after 1 week. After a 12-week of follow-up, wound healing rate, amputation rate, inpatient day, duration of antibiotics, reinfection rate, incidence of new ulcers, readmission rate, and reoperation rate, and cumulative wound healing rate using Kaplan-Meier curves were assessed.Results: After 1 week of treatment, the ozone therapy group showed higher VEGF, SOD, and T-AOC levels compared to the control group (P<0.05), while CRP, PCT, ESR, IL-6, TNF-α, MDA levels and bacterial types were lower (P<0.05). The ozone therapy group had a higher wound healing rate after a 12-week follow-up (P<0.05).Kaplan-Meier curves indicated a higher cumulative wound healing rate in the ozone therapy group (P<0.05). Additionally, the ozone therapy group had lower inpatient day, duration of antibiotics, reinfection rate, and readmission rate compared to the control group (P<0.05). Conclusion: Short-term ozone therapy is effective in promoting wound healing in DFUs by reducing inflammation, increasing growth factor levels, improving oxidative stress status, shortening healing time, and improving long-term prognosis. These findings suggest the potential of short-term ozone therapy as a valuable treatment modality for DFUs.